Kajian Nilai Pendidikan Hindu Dalam Ritual Aruh Ganal Bawanang Pada Masyarakat Meratus Di Kecamatan Piani Kabupaten Tapin Provinsi Kalimantan Selatan - Maskam Maskam; I Wayan Karya; Ervantia Restulita L. Sigai (Tampung Penyang, 2022)
The Aruh Ganal Bawanang ritual is a ritual of the Meratus Hindu Community in Piani District, Tapin Regency who strongly believes in the Ancestor which is held once a year, namely in July before the full moon, the Meratus community who strongly believes in their ancestors carry out the Aruh Ganal Bawanang ritual. The Aruh Ganal Bawanang ritual, if it is associated with the teachings of the Panca Yadnya, the Aruh Ganal Bawanang ritual is classified as the ritual of Dewa Yadnya, Pitra Yadnya and Bhuta Yadnya. The Aruh Ganal Bawanang ritual carried out by the Meratus Hindu community in Piani District who still adheres to the local Hindu religion. The implementation of the Aruh Ganal Bawanang Ritual by the Meratus Hindu community in the Piani Sub-district is still understood in the form of entrenched traditions and habits that have been passed down from generation to generation, without understanding and knowing the values ​​of Hindu education contained in the Aruh Ganal Bawanang ritual. Therefore, the research focuses more on the Study of Educational Values ​​in the Aruh Ganal Bawanang ritual in the Meratus Hindu community with the formulation of the problem: 1) How is the implementation of the Aruh Ganal Bawanang Ritual in Piani District, Tapin Regency. 2) What are the Ritual values ​​in Aruh Ganal Bawanang. 3) What are the implications of Aruh Ganal Bawanang Ritual Education in Piani District, Tapin Regency. The researcher aims to find out more about the Ritual of Aruh Ganal Bawanang. The theory used to determine the Ritual of Aruh Ganal Bawanang are: Symbol theory, Structural Functional theory and exchange theory. The methods used in this research are: descriptive method, qualitative analysis method, interview method, observation and documentation method. Based on the results of the study as follows: The Aruh Ganal Bawanang ritual, which starts with: 1) The Manabas Starting Ritual, 2) the Batabang Ritual 3.) the Manyalukut Ritual, 4) the Mamanduk and Mahayip Ritual, 5) the Bamata Umang Ritual, 6) the Mananam Banih Ritual, 7 ) Ritual of Merabon Banih Mandara, 8) Ritual of Ayahlas Banih, 9) Ritual of Manyampuk Banih Mawai (Rice flower begins to bear fruit), 10) Ritual of Mangatam, 11) Ritual of Aruh Ganal Bawanang, 12) Ritual of Babuat or Baancak Banih Kalulung. In Aruh Ganal Bawanang there are (1) religious education values, (2) social and cultural values, (3) ethical values, (4) religious tolerance values and (5) aesthetic values, while the educational implications are: (1) religious implications, (2) Cultural Implications, (3) Social Implications, and (4) Natural Resources Implications.